Comparison of culture, single and multiplex real‐time PCR for detection of Sabin poliovirus shedding in recently vaccinated Indian children. Issue 8 (6th March 2017) - Giri, Sidhartha; Rajan, Anand K.; Kumar, Nirmal; Dhanapal, Pavithra; Venkatesan, Jayalakshmi; Iturriza‐Gomara, Miren; Taniuchi, Mami; John, Jacob; Abraham, Asha Mary; Kang, Gagandeep
Abstract : Although, culture is considered the gold standard for poliovirus detection from stool samples, real‐time PCR has emerged as a faster and more sensitive alternative. Detection of poliovirus from the stool of recently vaccinated children by culture, single and multiplex real‐time PCR was compared. Of the 80 samples tested, 55 (68.75%) were positive by culture compared to 61 (76.25%) and 60 (75%) samples by the single and one step multiplex real‐time PCR assays respectively. Real‐time PCR (singleplex and multiplex) is more sensitive than culture for poliovirus detection in stool, although the difference was not statistically significant.